THE IMPACT OF COMPENSATION AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE IN THE ADMINISTRATION OF THE GENERAL BUREAU OF THE REGIONAL SECRETARIAT OF WEST JAVA PROVINCE - Septian Permana Putra; Deden Sutisna (SEAN Institute, 2023)
Human resources are an important factor because they have a very large role in determining the success of achieving organizational goals. An agency has a goal to be achieved, while to achieve its goals the company definitely needs employees who are responsible and have good performance. The General Bureau of the Regional Secretariat of West Java Province, where employee performance is an important matter to find out to what extent the agency's goals have been successful in realizing within a certain time and period. This study aimed to determine the effect of compensation and work motivation on employee performance in the Administrative Bureau of the General Secretariat of the Province of West Java. The method used is a quantitative method with a descriptive verification approach. The sample collection technique used was saturated sampling by observing and distributing questionnaires to 30 respondents. Data analysis techniques used validity test, reliability test, classic assumption test (normality test, multicollinearity test, and heteroscedasticity test), multiple linear regression test, and hypothesis testing (f test and t test). The results of this study indicate that compensation has a positive and significant effect on employee performance, while work motivation has a positive and significant effect on employee performance.